2016
DOI: 10.1371/journal.pone.0166774
|View full text |Cite
|
Sign up to set email alerts
|

Whole Body Vibration Treatments in Postmenopausal Women Can Improve Bone Mineral Density: Results of a Stimulus Focussed Meta-Analysis

Abstract: Whole body vibration treatment is a non-pharmacological intervention intended to stimulate muscular response and increase bone mineral density, particularly for postmenopausal women. The literature related to this topic is controversial, heterogeneous, and unclear despite the prospect of a major clinical effect.The aim of this study was to identify and systematically review the literature to assess the effect of whole body vibration treatments on bone mineral density (BMD) in postmenopausal women with a specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 31 publications
(87 reference statements)
2
60
0
3
Order By: Relevance
“…Vibration exercise is a new and effective measure to prevent muscular atrophy and osteoporosis [34]. Osteoporosis is a disorder described by low bone mass and structural deterioration of bone tissue leading to bone fragility and an increased risk of hip, spine, and wrist fractures [35]. The latter could be associated with osteoarthritis leading to several histopathological changes and determining an endogenous cellular response [2,36].…”
Section: Adaptive Responses Of Bone and Cartilage To Vibration Exposurementioning
confidence: 99%
“…Vibration exercise is a new and effective measure to prevent muscular atrophy and osteoporosis [34]. Osteoporosis is a disorder described by low bone mass and structural deterioration of bone tissue leading to bone fragility and an increased risk of hip, spine, and wrist fractures [35]. The latter could be associated with osteoarthritis leading to several histopathological changes and determining an endogenous cellular response [2,36].…”
Section: Adaptive Responses Of Bone and Cartilage To Vibration Exposurementioning
confidence: 99%
“…In the present study, the vibration, using the parameters analyzed, showed no signs of injury to the sciatic nerve after 4 or 8 weeks. This divergence with the studies mentioned above could be due to the difference in cumulative dose, which is described as the total time of exposure to vibration and considers the number of weekly sessions and the duration of the stimulus 14 . In studies by Baig, Guarino, Lipschutz, Winkelstein 18 and Kartha, Zeeman and Baig 17 , although the researchers used the vibration for only 7 days, they used twice the daily time of the present study.…”
Section: Discussionmentioning
confidence: 81%
“…The responses of therapy with a vibrating platform depend on the parameters to be used 13 , with time being a key variable, as prolonged exposure can cause damage to the tissue [14][15][16][17][18][19] . This prolonged exposure (daily and weekly) of the peripheral nerve to the vibration is widely studied in an occupational scope.…”
Section: Introductionmentioning
confidence: 99%
“…The intensity of WBVT mainly is regulated by the duration of each training session, the frequency, the amplitude and the body position as well as by exercises performed on the device [5][6][7]. One of the most important research questions regarding the use of WBVT is to identify the ideal composition of these parameters and the appropriate mode of vibration for each intention [7][8][9]. All training parameters and their interaction are resulting in a specific exercise stimulus, influencing the effects of the exercise [10].…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed, that such divergences might be due to between manufacturers and device types varying drives, the rigidity of used materials as well as possible software failures [9,11]. According to the available published literature, no published research results regarding potential divergences of the actually applied amplitude were identified.…”
Section: Introductionmentioning
confidence: 99%